Obstructive Sleep Apnea in Pediatrics and Adolescent Women: A Systematic Review of Sex-Based Differences Between Girls and Boys - Sofía Romero-Peralta; Cristina Rubio; María Castillo-García; Pilar Resano; Miguel Alonso; Esther Solano-Pérez; Laura Silgado; Esther Viejo-Ayuso; Leticia Álvarez-Balado; Olga Mediano (Children)
Background/Objectives: Obstructive sleep apnea (OSA) is marked by repetitive occurrences of upper airway (UA) obstruction during sleep. Morbidities impacting the metabolic, cardiovascular (CV) and neurological systems are correlated with OSA. Only a few studies have described the existence of different characteristics depending on sex and, to date, the girl phenotype in OSA pediatrics is not well known. The objective of this systematic review is to identify the specific phenotype of OSA in pediatric and adolescent females compared to males. Methods: A systematic review was performed. The terms “pediatric sleep apnea” and “sex differences” were used to look for publications using PubMed, the Cochrane Library and Web of Science. Inclusion criteria: (1) peer-reviewed journal articles written in English; (2) investigations conducted on individuals diagnosed with OSA; and (3) investigations providing information about sex differences. Exclusion criteria: (1) studies carried out with individuals aged 18 years and older; (2) studies involving a sample size of fewer than 10 patients; and (3) editorials, letters and case reports. Results: Fifteen studies were included and classified in sections related to sex-based differences. Conclusions: Limited information related to sex-based OSA differences in the pediatric population exists. These differences are conditioned by hormonal status, and are minimal in the premenarcheal period. Moreover, adolescent women present a lower prevalence of obesity and craniofacial alterations, lower OSA severity related to higher UA area and earlier tonsil regression. Hyperactivity is more frequent in boys. Some studies pointed to a higher risk of high diastolic blood pressure in girls than in boys.